Multi-omic Profiling Reveals that Intra-abdominal-Hypertension-Induced Intestinal Damage Can Be Prevented by Microbiome and Metabolic Modulations with 5-Hydroxyindoleacetic Acid as a Diagnostic Marker - Fang Li; Liuyiqi Jiang; Shuming Pan; Shaowei Jiang; Yiwen Fan; Chao Jiang; Chengjin Gao; Yuxin Leng (mSystems, 2022)
ABSTRACT Emerging evidence shows that modulation of the microbiome can suppress intra-abdominal hypertension (IAH)-induced intestinal barrier damage through the regulation of amino acid (AA) biosynthesis. Here, we investigated the protective effects of orally gavaged Lactobacillus acidophilus L-92 (L92) and a mixture of AA in rats with induced IAH. The results showed that both L92 and AA pretreatments effectively mitigated IAH-induced intestinal damage. Interestingly, L92 but not AA prevented metagenomic changes induced by IAH. Bacteroides fragilis, Bacteroides eggerthii, Bacteroides ovatus, Faecalibacterium prausnitzii, Prevotella, and extensively altered functional pathways were associated with L92-mediated host protection. Metabolomic profiling revealed that tryptophan metabolism was involved in both L92- and AA-mediated gut protection. The tryptophan metabolite 5-hydroxyindoleacetic acid (5-HIAA) is a sensitive biomarker for IAH in rats and patients with either gut-derived sepsis (n = 41) or all-source sepsis (n = 293). In conclusion, we show that microbiome and metabolic modulations can effectively prevent IAH-induced intestinal damage and that 5-HIAA is a potential metabolic marker for IAH and sepsis. IMPORTANCE Gut protection through modulation of the microbiome for critically ill patients has been gaining much attention recently. Intra-abdominal hypertension (IAH) is a prevailing clinical feature of acute gastrointestinal injuries in critically ill patients, characterized by nonspecific intestinal barrier damage. Prolonged IAH can induce or aggravate the development of sepsis and multiorgan dysfunctions. Therefore, the prevention of IAH-induced damage in rats through microbiome and metabolic interventions by commercially available L92 and AA treatments and the identification of 5-HIAA as an important marker for IAH/sepsis have important clinical implications for the treatment and early diagnosis of critically ill patients.